Molecular Orientation Effect on the Photodetachment of a Diatomic Molecular Anion (Journal of Atomic and Molecular Sciences, 2015)
The interference effect in the photdetachment of a diatomic molecular anionis investigated theoretically for different molecular orientation by using the two-centermodel. An analytic formula is presented for the photodetached electron fluxdistribution at a given observation plane. Taking $H^-_2$ as an example, we calculate theelectron flux distribution and photodetachment cross section for arbitrary molecularorientation. The results show that the molecular orientation has great influence on thephotodetachment of the diatomic molecular anion. At certain molecular orientation,the interference in the electron flux distribution is totally constructive; while at someother orientations, the interference is destructive. For molecular orientation along thelaser light polarization, the oscillation amplitude in the photodetachment cross sectionis the largest; however, for the molecular orientation perpendicular to the laser lightpolarization, no oscillation appears in the cross section. Our studies suggest that wecan control the photodetachment process of the molecular negative ion by changingthe molecular orientation. Our researches will be helpful for the theoretical and experimentalstudy of the photodetachment of molecular anion.
Keywords: molecular orientation; photodetachment; interference; two-center model.